Implementasi Penggunaan Media Wordwall Pada Mata Pelajaran Pai Untuk Meningkatkan Motivasi Dan Minat Belajar Siswa di SMPN 3 Kecamatan Guguak - Azizah Rahma Pinta; Hamdi Abdul Karim; Linda Trisna (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
Many students have not fully participated in PAI learning optimally, due to the lack of use of learning media that is able to accommodate students' motivation and interest in carrying out learning in class. Therefore, there is a need for interactive learning media that is able to form students' enthusiasm and interest in learning in PAI subjects. One of the interactive learning media that can be used is wordwall media. This article was written based on Field Experience Practice (PPL) activities using qualitative research with a descriptive approach. Qualitative research is research intended to understand certain phenomena. Research data collection techniques can be carried out through several methods, such as observation, interviews and documentation. Observation data shows a higher level of student involvement and active participation during PAI learning. Implementing Wordwall encourages students to complete their assignments immediately. Students show a greater willingness to ask questions and seek clarification during PAI learning. The findings show that the application of Wordwall media at SMPN 3 Guguak District has a positive effect on students' motivation and interest in learning PAI. The interactive and gamified nature of Wordwall engages students, encourages active participation, and fosters a positive learning environment.